BCG-Prime and boost with Esx-5 secretion system deletion mutant leads to better protection against clinical strains of Mycobacterium tuberculosis. Issue 45 (21st October 2020) - Tiwari, Sangeeta; Dutt, Taru S.; Chen, Bing; Chen, Mei; Kim, John; Dai, Annie Zhi; Lukose, Regy; Shanley, Crystal; Fox, Amy; Karger, Burton R.; Porcelli, Steven A.; Chan, John; et al.
Abstract: Although vaccination with BCG prevents disseminated forms of childhood tuberculosis (TB), it does not protect against pulmonary infection or Mycobacterium tuberculosis ( Mtb ) transmission. In this study, we generated a complete deletion mutant of the Mtb Esx-5 type VII secretion system ( Mtb Δesx-5) . Mtb Δesx-5 was highly attenuated and safe in immunocompromised mice. When tested as a vaccine candidate to boost BCG-primed immunity, Mtb Δesx-5 improved protection against highly virulent Mtb strains in the murine and guinea pig models of TB. Enhanced protection provided by heterologous BCG-prime plus Mtb Δesx-5 boost regimen was associated with increased pulmonary influx of central memory T cells (TCM ), follicular helper T cells (TFH ) and activated monocytes. Conversely, lower numbers of T cells expressing exhaustion markers were observed in vaccinated animals. Our results suggest that boosting BCG-primed immunity with Mtb Δesx-5 is a potential approach to improve protective immunity against Mtb . Further insight into the mechanism of action of this novel prime-boost approach is warranted.